Patients' beliefs and behaviors related to treatment adherence in patients with asthma requiring maintenance treatment in Asia. (1st April 2014) - Chiu, K.-C.; Boonsawat, W.; Cho, S.-H.; Cho, Y. J.; Hsu, J.-Y.; Liam, C.-K.; Muttalif, A. R.; Nguyen, H. D.; Nguyen, V. N.; Wang, C.; Kwon, N.
Abstract: Objectives : To identify patients' beliefs or behaviors related to treatment adherence and to assess association between asthma control and adherence in Asian patients with asthma. Methods: We conducted a cross-sectional observational study of adult patients with asthma from specialist clinics in six Asian countries. Patients who were deemed by their treating physicians to require a maintenance treatment with an inhaler for at least 1 year were recruited. Patients completed a 12-item questionnaire related to health beliefs and behaviors, the 8-item Morisky Medication Adherence Scale (MMAS-8), the Asthma Control Test (ACT™), and the Standardized Asthma Quality of Life Questionnaire (AQLQ-S). Results : Of the 1054 patients recruited, 99% were current users of inhaled corticosteroids. The mean ACT score was 20.0 ± 4.5 and 64% had well-controlled asthma. The mean MMAS-8 score was 5.5 ± 2.0 and 53% were adherent. Adherence was significantly associated with patients' understanding of the disease and inhaler techniques, and with patients' acceptance of inhaler medicines in terms of benefits, safety, convenience, and cost ( p < 0.01 for all). In multivariate analysis, three questions related to patients' acceptance of inhaler medicines remained significantly associated with poor adherence, after adjusting for potential confounders: "I am not sure inhaler type medicines work well" ( p = 0.001), "Taking medicines more than once a day is inconvenient" ( p = 0.002), and "Sometimes I skip my inhaler to use it over a longer period" ( p < 0.001). Conclusions : Our study showed that patients' acceptance of the benefits, convenience and cost of inhaler medications have a significant impact on treatment adherence in the participating Asian countries.